The Use of Big Book as a Literation Based Teaching Material to Improve Reading Skills in Inclusive Primary School - Nuri Annisa; Nofrita Nofrita (Universitas Sebelas Maret, 2019)
Literacy is one of life skills that cannot be separated from an individual. Starting from the low literacy ability of elementary school students in Indonesia, especially the ability to read, researchers try to find alternatives that can help students in making literacy activities into fun activities. One of the causes of the low literacy in Indonesia is the difficulty in obtaining fun teaching materials, so that students have assumed that literacy is only limited to school assignments. One of the efforts that the writer did was to use literacy-based teaching materials. The purpose of this study is to find out how the application of literacy-based teaching materials especially big books and whether literacy-based teaching materials can improve students' reading skills. In addition, teachers are expected to be able to make improvements in planning and implementation of learning activities and researchers are expected to be able to collaborate with practitioners in the field, thereby increasing insight and input for teaching in LPTK. This study uses a quantitative approach. The results showed that big books can improve students' reading skills in elementary school.